2007
DOI: 10.1128/jvi.01887-06
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Infection Alters Peripheral T-Cell Homeostasis in Children with Acute Diarrhea

Abstract: The patterns of gene expression and the phenotypes of lymphocytes in peripheral blood mononuclear cells (PBMC) from children with diarrhea caused by rotavirus and healthy children were compared by using DNA microarray, quantitative PCR, and flow cytometry. We observed increased expression of a number of genes encoding proinflammatory cytokines and interferon or interferon-stimulated proteins and demonstrated activation of some genes involved in the differentiation, maturation, activation, and survival of B lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 55 publications
7
44
2
1
Order By: Relevance
“…In agreement with previous reports of RV-infected splenocytes from mice and PBMC from children with acute RV- induced gastroenteritis (6,70), RV induced the CD69 expression of a significant fraction of CBC when cells were infected as a component of whole PMBC, but there was low or no activation and ASC differentiation observed when purified CBC or IBC were infected (Fig. 4).…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with previous reports of RV-infected splenocytes from mice and PBMC from children with acute RV- induced gastroenteritis (6,70), RV induced the CD69 expression of a significant fraction of CBC when cells were infected as a component of whole PMBC, but there was low or no activation and ASC differentiation observed when purified CBC or IBC were infected (Fig. 4).…”
Section: Discussionsupporting
confidence: 81%
“…Elevated levels of inflammatory cytokines correlate directly with the severity and frequency of diarrheal episodes during the acute phase of rotavirus infection in naturally infected children (33,34) and are also observed in experimentally infected gnotobiotic pigs (35,36). Therefore, the observations reported here are consistent with markers of systemic inflammation observed during rotavirus infection in vivo.…”
Section: Discussionsupporting
confidence: 80%
“…The frequencies of blood CD4+ and CD8+ T cells were reduced or significantly reduced in the VirHRV infected pigs compared to mock-inoculated control pigs at PID28. A recent study of children with acute rotavirus diarrhea also reported moderate to severe reduction in the frequencies of CD4+ and CD8+ T cells from peripheral blood [53]. The reduction in frequency of T cells in children was only detected in the acute-phase blood samples.…”
Section: Discussionmentioning
confidence: 97%
“…This difference between rotavirus infected Gn pigs and children may be due in part to the Gn status of pigs that lack of commensal microflora or environmental antigen stimulation may have delayed the recovery from the VirHRV-induced T cell lymphopenia. The mechanism for the rotavirus-induced T cell lymphopenia in pigs and children are unclear and requires further studies [53].…”
Section: Discussionmentioning
confidence: 99%